Deceleration of glycometabolism impedes IgG‐producing B‐cell‐mediated tumor elimination by targeting SATB1. Issue 1 (10th October 2018) - Liu, Jiajing; Li, Yifan; Lu, Zhou; Gu, Jie; Liang, Yun; Huang, Enyu; Wang, Zhiming; Zhang, Hushan; Wang, Luman; Zhang, Dan; Yu, Hongxiu; Liu, Ronghua; et al.
Summary: B lymphocytes, known as antibody producers, mediate tumor cell destruction in the manner of antibody‐dependent cell‐mediated cytotoxicity; however, their anti‐tumor function seems to be weakened during tumorigenesis, while the underlying mechanisms remain unclear. In this study, we found that IgG mediated anti‐tumor effects, but IgG‐producing B cells decreased in various tumors. Considering the underlying mechanism, glycometabolism was noteworthy. We found that tumor‐infiltrating B cells were glucose‐starved and accompanied by a deceleration of glycometabolism. Both inhibition of glycometabolism and deprivation of glucose through tumor cells, or glucose‐free treatment, reduced the differentiation of B cells into IgG‐producing cells. In this process, special AT‐rich sequence‐binding protein‐1 (SATB1) was significantly silenced in B cells. Down‐regulating SATB1 by inhibiting glycometabolism or RNA interference reduced the binding of signal transducer and activator of transcription 6 (STAT6) to the promoter of germline C γ gene, subsequently resulting in fewer B cells producing IgG. Our findings provide the first evidence that glycometabolic inhibition by tumorigenesis suppresses differentiation of B cells into IgG‐producing cells, and altering glycometabolism may be promising in improving the anti‐tumor effect of B cells. Abstract : IgG‐producing B cells exerted an anti‐tumor effect, but dramatically decreased in various tumors. Glucose deprivation caused by tumorigenesis down‐regulated the glucose metabolism of B cells and then impaired their generation into IgG‐producing B cells. SATB1, known as a cell‐type‐specific 'genomic organizer', was down‐regulated in the glucose‐starved B cells and responsible for the deficiency generation of IgG‐producing B cells in tumors.